Framing TOWS as Marketing Strategy Determiner of Medical Equipment in PT. Tawada Healthcare Jakarta Indonesia - Asari, Asari; Puspitaloka Mahadewi, Erlina; Marti Ayu, Ira; Shorayasari, Susi (Publisher Cv. Inara, 2022)
The present study reports the comprehensive framing study around healthcare marketing stategy, inside the era of globalization has led to intense competition in various industrial fields, including the medical equipment in healthcare industry. PT. Tawada Healthcare was founded in 1999 with the aim of becoming the most integrated, reliable and customer-based healthcare provider in Indonesia. Over the years the company added a variety of different brands and products to its portfolio to serve a wider customer base, the company focused on providing the best customer experience and offering the highest quality products to customers in Indonesia. currently represents 20 major international principals and has a network to market its products throughout the country, covering provinces and major cities. It has 13 branches including its head office in Jakarta. The decline in sales of orthopedic implant medical devices at PT. Tawada Healthcare Jakarta in 2020 due to the pandemic impact of 41% of the total sales target of orthopedic implants in 2020 of 120,000,000,000 IDR. The cause of the decline in sales of orthopedic implant medical devices at PT. Tawada Healthcare is the rise of competitors of similar orthopedic implant medical device companies. The covid19 pandemic that hit the world, including Indonesia, resulted in a decrease in the budget for the procurement of orthopedic implant medical devices from the government because the budget was allocated for handling the covid19 pandemic and the decreasing demand for orthopedic implant medical devices from users due to the covid19 pandemic. This study aims to provide an overview of the TOWS (threat, opportunity, weakness and strength) method approach as an alternative solution and determine the strategy for selling medical devices at PT. Tawada Healthcare in 2021-2022.